Cobalt‐Phthalocyanine‐Derived Molecular Isolation Layer for Highly Stable Lithium Anode. (26th July 2021) - Dai, Hongliu; Dong, Jing; Wu, Mingjie; Hu, Qingmin; Wang, Dongniu; Zuin, Lucia; Chen, Ning; Lai, Chao; Zhang, Gaixia; Sun, Shuhui
Abstract: The uneven consumption of anions during the lithium (Li) deposition process triggers a space charge effect that generates Li dendrites, seriously hindering the practical application of Li‐metal batteries. We report on a cobalt phthalocyanine electrolyte additive with a planar molecular structure, which can be tightly adsorbed on the Li anode surface to form a dense molecular layer. Such a planar molecular layer cannot only complex with Li ions to reduce the space charge effect, but also suppress side reactions between the anode and the electrolyte, producing a stable solid electrolyte interphase composed of amorphous lithium fluoride (LiF) and lithium carbonate (LiCO3 ), as verified by X‐ray absorption near‐edge spectroscopy. As a result, the Li|Li symmetric cell exhibits excellent cycling stability above 700 h under a high plating capacity of 3 mAh cm −2 . Moreover, the assembled Li|lithium iron phosphate (LiFePO4, LFP) full‐cell can also deliver excellent cycling over 200 cycles under lean electrolyte conditions (3 μL mg −1 ). Abstract : A planar molecular cobalt phthalocyanine was introduced into the bare electrolyte of a Li|LiFePO4 full‐cell under lean electrolyte conditions (3 μL mg −1 ), thereby protecting the cathode and anode electrodes at the same time, and enhancing the electrochemical performance. X‐ray absorption fine structure was used to verify the protective mechanism of additives at the cathode and anode electrodes.